2018
DOI: 10.3389/fimmu.2018.01970
|View full text |Cite
|
Sign up to set email alerts
|

CD18 Regulates Monocyte Hematopoiesis and Promotes Resistance to Experimental Schistosomiasis

Abstract: Infection with Schistosoma mansoni causes a chronic parasitic disease that progress to severe liver and gastrointestinal damage, and eventually death. During its development into mammalian hosts, immature schistosomula transit through the lung vasculature before they reach the liver to mature into adult worms. A low grade inflammatory reaction is induced during this process. However, molecules that are required for efficient leukocyte accumulation in the lungs of S. mansoni-infected subjects are unknown. In ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 47 publications
1
22
0
1
Order By: Relevance
“…Based on the differential expression of surface markers, monocytes are classified as: inflammatory monocytes (classical) (mouse: Ly6C high CCR2 + CX 3 CR1 low ; human: CD14 high CD16 − ), which are robustly recruited to sites of inflammation (Geissmann et al, 2003), but return to the bone marrow after 3 days under steady state (Varol et al, 2007); and patrolling monocytes (non-classical) (mouse: Ly6C low CCR2 low CX 3 CR1 high; human: CD14 low/− CD16 high ), which patrol blood vessels and remain in the circulation for as long as 7 days (Auffray et al, 2007; Figure 2). Recently, we showed that low expression of CD18 (common subunit of β2 integrins) was associated with a reduction of monocyte subsets in bone marrow and blood of mice infected with S. mansoni (Souza et al, 2018). This correlated with increased parasite burden, egg deposition and mortality of mice.…”
Section: Origin and Function Of Monocytes During Schistosomiasismentioning
confidence: 97%
See 1 more Smart Citation
“…Based on the differential expression of surface markers, monocytes are classified as: inflammatory monocytes (classical) (mouse: Ly6C high CCR2 + CX 3 CR1 low ; human: CD14 high CD16 − ), which are robustly recruited to sites of inflammation (Geissmann et al, 2003), but return to the bone marrow after 3 days under steady state (Varol et al, 2007); and patrolling monocytes (non-classical) (mouse: Ly6C low CCR2 low CX 3 CR1 high; human: CD14 low/− CD16 high ), which patrol blood vessels and remain in the circulation for as long as 7 days (Auffray et al, 2007; Figure 2). Recently, we showed that low expression of CD18 (common subunit of β2 integrins) was associated with a reduction of monocyte subsets in bone marrow and blood of mice infected with S. mansoni (Souza et al, 2018). This correlated with increased parasite burden, egg deposition and mortality of mice.…”
Section: Origin and Function Of Monocytes During Schistosomiasismentioning
confidence: 97%
“…Monocytes promote resistance to schistosomiasis (Nascimento et al, 2014;Souza et al, 2018;de Souza et al, 2019). Indeed, inflammatory monocyte depletion causes a severe weight loss and disrupts a protective Th2 response during S. mansoni infection (Nascimento et al, 2014).…”
Section: Origin and Function Of Monocytes During Schistosomiasismentioning
confidence: 99%
“…Infiltrating leukocytes were isolated from mice lung using the protocol reported by Souza and colleagues [14]. Briefly, the upper right lung lobule was collected, minced with sterile scissors in RPMI 1640 medium, and treated with digestion buffer containing 0.05 mg/mL liberase (Roche-Basel, Switzerland) and 0.5 mg/mL DNase (Sigma-Aldrich) for 45 min, at 37 • C, under shaking at 2000 rpm.…”
Section: Analysis Of Lung Leukocyte Populationmentioning
confidence: 99%
“…The same cellular suspension used for fungal burden determination in lungs was used for the immunophenotyping of lung parenchyma cells by flow cytometry, as previous described [45,46]. The cell suspension was filtered in a sterile filcon syringe type (BD Bioscience-San Jose, CA, USA), submitted to red blood cells lysis with ammonium-chloride-potassium (ACK) solution and the number of total cells isolated from lung parenchyma was determined in a Neubauer chamber.…”
Section: Flow Cytometrymentioning
confidence: 99%